Pharmacoeconomics of Antidiabetic Drugs - Chandra, Dr. Amrish (Asian Journal of Pharmaceutics (AJP), 2019)
Context: Diabetes mellitus is a severe chronic lifelong disease due to a combination of insulin release and insulin secretory defect characterized by polyuria, polydipsia, and polyphagia. Antidiabetic drugs are available in different formulations that create wide price variation in regulated (India) and less regulated market (US). Objective: The objective of this study was to analyze price variation of unit dosage form manufactured by different companies for the same formulation with the same strength in both markets by calculation percentage price variation among the market. Materials and Methods: Cost of particular unit drug manufactured by different companies, in the same strength, was obtained from â€œcurrent index of medical specialtiesâ€ and â€œIndian Drug Reviewâ€ for regulated market and from â€œGoodRXâ€ and â€œOnline Pharmaciesâ€ for less regulated market in both INR and USD. Results: However, percentage price variation is less in the US than in India, but prices are extremely high. In India, sitagliptin (50 mg) shows maximum price of 38.43 INR (0.5910 USD), whereas glibenclamide (2.5 mg) shows minimum price of 0.26 INR (0.0040 USD); in the US market, sitagliptin shows maximum price of 346.77 INR (5.3333 USD), whereas glipizide (2.5 mg) shows minimum price of 13 INR (0.1999 USD). Conclusion: Our findings revealed that the prices of various antidiabetic formulations show great variation. Modification in price regulation is required in the US to reduce unfair burden on both patient and health-care system.